Integration of Smart Class Control System Using Amazon Echo Dot with Artificial Neural Networks - Januar, Teddy; Rabi, Abd.; Prasetya, Dwi Arman (SENATIK STT Adisutjipto, 2019)
Development of a class resource system that is integrated with the system that is the application-based system. One system that can be used is the Smart Class. Smart Class is a system that offers control of electronic equipment in the classroom using voice command control with a device that is Smart Speaker called Amazon echo dot which is used to facilitate the use of electronic devices in classrooms using Raspberry Pi Microcontroller technology by embedding smart class artificial neural network technology. With maximum performance at 1500ms to 2000ms on all conditions both sensors and actuators by iterating simultaneously 500 times with two hidden layers and the number of cells of each hidden layer is 9 and 5.